Relationship between muscle torque and performance in special and specific exercises in young weightlifters - Szyszka, P.; Jaszczuk, J.; Sacharuk, J.; Parnicki, F.; Czaplicki, A. (Polish Journal of Sport and Tourism, 2016)
Introduction. The aim of the current study was to examine the relationship between knee and elbow isometric muscle torque values and the results obtained in special and specific exercises in young weightlifters. Material and methods. The study involved eight young weightlifters (age: 19.9 +/- 4.3 years; height: 176.8 +/- 10.6 cm; weight: 69.0 +/- 19.7 kg . pretest, 70.9 +/- 21.6 . posttest). Their performance put them in the second and third top classes of weightlifters their age according to the Polish norms for weightlifting (the so-called national class and first clss in the Polish system, which are lower than the international class). The differences between the values obtained in the first measurement of torque performed at the beginning of the preparation period and those obtained at the beginning of the immediate pre-competition period were compared with the differences in the maximal load lifted in special and specific exercises. Results. The training that the weightlifters underwent during the preparation period caused a significant increase in the relative torque values of the knee extensors (0.56 Nm/kg on average, p . 0.047) and those of the elbow flexors (0.35 Nm/kg, p . 0.0002). Significant differences (p . 0.05) were observed between the results obtained in all of the special and specific exercises examined. A statistically significant relationship was also found between the changes in relative torque values and the results achieved in special and specific exercises. Conclusions. The regression equations derived in the study can help predict sports performance outcomes based on the results of laboratory tests.